Effect of Chitosan Hydrogel inclusion on Centesimal Composition of Pangasius (Pangasianodon hypophthalmus) (Sauvage, 1878) Emulsion Sausages under Refrigerated Storage - Chattopadhyay, Kasturi; Martin Xavier, K. A.; Layana, P.; Balange, A. K.; Nayak, B. B. (Fishery Technology, 2020)
Chitosan is a diverse polymer of biological originhaving a widespread application in food industry.The cross linking properties of chitosan beneficiallyaffects the protein-carbohydrate interactions whichin turn enhances the functional properties inemulsion based meat products. In this context, thepresent study was conducted to incorporate chitosanhydrogel in varying ratio (0, 0.125, 0.25, 0.375 and0.5%) into fish mince (Pangasianodon hypophthalmus)(Sauvage, 1878) sausages in order to develop afunctional sausage products upon storage. Sampleswithout chitosan additions showed a significant andrapid decline in the crude protein content after the24th day of storage in contrast to the chitosan treatedgroups where a slower rate of decline was foundonly after 48th days of storage. Fat content alsoshowed greater stability in the values in case ofchitosan added samples upto 48th days of storagein comparison to the control samples where a rapiddecrease in the contents were observed. However,ash and carbohydrate content showed minor variationsamong the treatment and control groupsthough all were showing decreasing trend uponstorage. The comparative analysis of centisimalcomposition of the produced sausages showed thatinclusion of chitosan gel had a significant effect(p